Exchange rates and import prices in Finland: estimation of exchange rate pass-through - Mika Kuismanen (Bank of Finland, 1995)
The purpose of this study is to examine the relationship between import prices and exchange rates in Finland.The concept of pass-through is associated with how prices of internationally traded goods are affected by changes in exchange rates. Pass-through is said to be complete when the exporter of the good does not adjust prices in his home currency.This means that exchange rate fluctuations are totally reflected in local import prices abroad.On the contrary, if import prices in local currencies remain stable, it is the prices received by exporters that must adjust to exchange rate movements.This paper presents a simple static theoretical model for pass-through.After that, some estimation results for Finnish import prices are shown.Estimation results are mixed, but it is evident that depreciation of markka increases import prices.
URN:NBN:fi:bof-20140807286
Keywords: 330